Eksistensi Tari Mahelat Lebo karya Sanggar Permata Ije Jela Kabupaten Barito Kuala - Alifia Pipit Safitri; Gita Kinanthi Purnama Asri (Adinda); Andy Wijaya (STKIP PGRI BANJARMASIN, 2022)
Sanggar Permata Ije Jela located in Barito Kuala Regency, has a creative dance that is set in the culture of the Bakumpai Dayak community, namely the Mahelat Lebo dance. The presence of this tariff provides various positive impacts. This study aims to 1) Knowing the background of the creator of the Mahelat Lebo Dance 2) Knowing the form of presentation of the Mahelat Lebo Dance. 3) Knowing the existence of Mahelat Lebo Dance and the factors that influence it. The research method used is descriptive qualitative. Data collection techniques by means of interviews, observation, documentation, and literature study. The result of the research is that the Mahelat Lebo Dance is a dance creation based on the local culture and traditions of the Bakumpai Dayak, to take part in the 2010 Regional Dance Works Festival (FKTD). The existence of the Mahelat Lebo dance can be seen from the form of presentation that emphasizes the Bakumpai people, the frequency of this dance performance is quite within the reach of national and international scales from 2015 to 2021. So there is no doubt about the achievements he has achieved. Internal supporting factors such as creativity and supporting factors are support from the government, external inhibiting factors including techniques and external inhibiting factors are the covid-19 outbreak.